2014
DOI: 10.5897/ajar2014.8636
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study on foot and mouth disease in cattle: Seroprevalence and risk factor assessment in Kellem Wollega Zone, West Ethiopia

Abstract: . Seropositivity was significantly varied with sex and district of cattle (P < 0.05). The odds of being seropositive for female cattle was observed to be 2.05 times of the male cattle (OR; 2.05, 95% CI: 1.22 -3.43) and Cattle from Sayo district had significantly higher seroprevalence than dale sadi cattle (OR; 2.58, 95% CI: 1.37 -4.87). In conclusion, the result of this study showed that FMD is an important cattle disease in the study area necessitating further investigation and characterization of the circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
1
1
1
Order By: Relevance
“…The present study revealed that FMD is one of the most important cattle diseases in the study areas with an estimated seroprevalence of 19.8% (n = 76/384) at animal level and 56.9% (n = 41/72) at herd level in three selected districts of afar region. In our study finding, the overall seroprevalence of FMDV at individual animal was consistent with previous seroprevalence results of 21% in Borana pastoral area (Rufael et al., 2008), 21% in Borana zone, and Guji zone (World Organisation for Animal Health, 2013), 21% in kellema Wollega zone (Fanta et al., 2014). In contrast to the current study finding, relatively lower seroprevalence of FMD was previously reported with various prevalence magnitude, such as 13%, in selected districts of western Ethiopia (Asresie & Zemedu, 2015), 10.88% in some district of eastern showa zone, Oromia region (Dinaol et al., 2016), 12.05% in the Bench Maji zone, Southern Ethiopia (Gelaye et al., 2009), 8.8% in South Omo Zone (Molla et al., 2010), 9.5% in indigenous cattle of southern Ethiopia (Megersa et al., 2009), 5.53% on quarantined bulls for export at Nazareth and Dire Dawa stations (Bedru, 2006), and 4.8% in selected districts of western Oromia region (Milkessa et al., 2016).…”
Section: Discussionsupporting
confidence: 92%
“…The present study revealed that FMD is one of the most important cattle diseases in the study areas with an estimated seroprevalence of 19.8% (n = 76/384) at animal level and 56.9% (n = 41/72) at herd level in three selected districts of afar region. In our study finding, the overall seroprevalence of FMDV at individual animal was consistent with previous seroprevalence results of 21% in Borana pastoral area (Rufael et al., 2008), 21% in Borana zone, and Guji zone (World Organisation for Animal Health, 2013), 21% in kellema Wollega zone (Fanta et al., 2014). In contrast to the current study finding, relatively lower seroprevalence of FMD was previously reported with various prevalence magnitude, such as 13%, in selected districts of western Ethiopia (Asresie & Zemedu, 2015), 10.88% in some district of eastern showa zone, Oromia region (Dinaol et al., 2016), 12.05% in the Bench Maji zone, Southern Ethiopia (Gelaye et al., 2009), 8.8% in South Omo Zone (Molla et al., 2010), 9.5% in indigenous cattle of southern Ethiopia (Megersa et al., 2009), 5.53% on quarantined bulls for export at Nazareth and Dire Dawa stations (Bedru, 2006), and 4.8% in selected districts of western Oromia region (Milkessa et al., 2016).…”
Section: Discussionsupporting
confidence: 92%
“…This study agreed with the previous report from the Borana zone 53.6% [ 15 ] and 52.8% in Dire district [ 16 ]. However, the current study estimated prevalence was higher than previous reports in different parts of the country; 41.5% in the eastern Tigray region [ 17 ], 8.9% in South Omo Zone [ 18 ], 14.3% in the Amhara region [ 19 ], 21.4% in Kellem Wollega zone [ 20 ], and 26.8% in Adama [ 21 ]. These variations in prevalence reports could be due to differences in agro-climatic conditions, animal management systems as well as disease prevention practices.…”
Section: Discussioncontrasting
confidence: 85%
“…Based on data over the years 2007-2012, annual district level incidence of FMD outbreak was estimated at 0.24, 0.39 and 0.85 per district year in the crop livestock mixed, pastoral and market-oriented districts, respectively, and the outbreaks were caused by serotypes O, A, SAT 2 and SAT 1 (Jemberu et al, 2016). Serological studies of FMD undertaken in different parts of the country reported seroprevalence ranging from 5.6% to 24.2% (Desissa, Tura, Mamo, & Rufae, 2014;Jenbere, Etana, & Negussie, 2011;Mekonen, Beyene, Rufael, Feyisa, & Abunna, 2011;Mesfine, Nigatu, Belayneh, & Jemberu, 2019;Mohamoud, Tessema, & Degefu, 2011;Zerabruk, Romha, & Rufael, 2014).…”
Section: Introductionmentioning
confidence: 99%